MedPath: A process-based modeling language for designing care pathways. (February 2021) - Trajano, Iago Avelino; Ferreira Filho, João Bosco; de Carvalho Sousa, Flávio Rubens; Litchfield, Ian; Weber, Philip
Highlights: Doctors can benefit from simple DSLs that are less verbose and closer to the sketches they make manually when modeling care pathways. Specifying the types of activities in a medical action flow improve organization and disposition of medical activities as a process-based flow. Model-Based Engineering can fully translate the concepts of care pathways into a programmable artifact (a Domain Specific Language). MedPath is currently employed in both hospital and clinical care, having practical use one of its validation metrics. Abstract: Context: Medical professionals and hospitals promote solutions like care pathways and Health Information Systems (HIS) to support medical conduct and improve the quality of medical care. Purpose: This study proposes MedPath: a Domain Specific Language (DSL) for modeling care pathways based on the paradigms of Model-Based Engineering (MBE) that can be integrated into software solutions. Procedures: We have developed MedPath's abstract syntax with the Eclipse Modeling Framework by employing Ecore technology and concrete syntax with the Eclipse Sirius. Findings: We have modeled over 85 care pathways that are in use in 45 hospitals in Brazil. MedPath-originated pathways have been used over 3.2 million times since October 2017. We conducted a survey among the professionals who used MedPath to evaluate user satisfaction. Conclusions: We believe MedPath can translate any care pathway into an action flow with its current abstractions. MedPath makes care pathways more easily integrated into HIS and electronic patient records, as it enables programmatic modeling and generates consumable artifacts.